Modélisation tridimensionnelle des remontées de nappe et inondations au Val d’Avaray - Poligot-Pitsch, Stéphanie; Sergent, Philippe; Dhatt, Gouri (European Journal of Computational Mechanics, 2003)
Dikes of earth called levees protect independent floodplains called "vals" of the Loire river in France that lie lower than the water level during floods. Infiltration through these levees leads to the flooding of floodplains not by overtoping but by phreatic surface rising. In order to better assess the exfiltration flow leading to the flooding of "vals", groundwater rising in Val d’Avaray and exchanges between the groundwater and surface flow are modeled. A tridimensional finite elements model of groundwater flow is coupled with a bidimensional finite elements surface flow model. Special attention is paid to the validation of the coupling on analytical benchmarks and to the choice of the time steps used for the two models.